Shape-Dependent Locomotion of DNA-Linked Magnetic Nanoparticle Films - Ko, Jein; Kim, Jongwook; Ki, Kanghyun; Moon, Soyoon; Jeon, Hyunjin; Park, Jin Hyeok; Golla, Murali; Chun, Chan Joo; Kim, Jong Sik; Lee, Anna; Kim, Hyoungsoo; Park, Sarah S.; et al. (Nano Letters, 2025)
The shape-dependent aero- and hydro-dynamics found in nature have been adopted in a wide range of areas spanning from daily transportation to forefront biomedical research. Here, we report DNA-linked nanoparticle films exhibiting shape-dependent magnetic locomotion, controlled by DNA sequences. Fabricated through a DNA-directed layer-by-layer assembly of iron oxide and gold nanoparticles, the multifunctional films exhibit rotational and translational motions under magnetic fields, along with reversible shape morphing via DNA strand exchange reactions. Notably, the shape of the film significantly influences its magnetic responsiveness, attributable to shape-dependent drag forces acting on mesoscopic films. The distinctive shape dependence combined with the shape-changing capability offers an approach to regulate magnetic locomotion within a constant magnetic field, as demonstrated here through the go and stop motion of nanoparticle films without altering the magnetic field.
Keywords: Biomedical research; Gold nanoparticle; Iron oxide nanoparticle; Layer by layer; Layer-by-layer assemblies; Locomotion; Magnetic-field; Nanoparticle films; Oxide nanoparticles; Superparamagnetics; DNA; Ferric Compounds; Gold; Magnetic Fields; Magnetite Nanoparticles; Metal Nanoparticles; DNA; Iron oxide nanoparticle; Layer-by-layer; Locomotion; Self-assembly; Superparamagnetic